2004
DOI: 10.1111/j.1440-1827.2004.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of thymidylate synthase, p16INK4a, cyclin‐dependent kinase 4 and cyclin D1 in colorectal cancers receiving preoperative chemotherapy: Significance of p16INK4a‐mediated cellular arrest as an indicator of chemosensitivity to 5‐fluorouracil

Abstract: High expression of thymidylate synthase (TS) is allegedly associated with the chemoresistance to 5-fluorouracil (5-FU) in colorectal cancers. However, low TS expression does not necessarily imply chemosensitivity. Inactivation of p16(INK4a) correlates with poor prognosis in various cancers. We immunohistochemically evaluated the relationship between the expression of TS, p16(INK4a), CDK4 and cyclin D1 and the effect of 5-FU-based chemotherapy in colorectal cancers. After antigen retrieval, immunoperoxidase sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…As shown in this report, TS expression is decreased both by small molecule inhibitors of CDK4 and following over-expression of p16INK4A. Interestingly, it has been previously shown that tumour tissue from patients who responded to fluoropyrimidine-based treatment expressed high levels p16INK4A (Kamoshida et al, 2004). Since we have shown that CDK4 regulates TS expression, high levels of p16INK4A would be expected to decrease TS levels and to sensitise cells to anti-TS drugs.…”
Section: Discussionsupporting
confidence: 67%
“…As shown in this report, TS expression is decreased both by small molecule inhibitors of CDK4 and following over-expression of p16INK4A. Interestingly, it has been previously shown that tumour tissue from patients who responded to fluoropyrimidine-based treatment expressed high levels p16INK4A (Kamoshida et al, 2004). Since we have shown that CDK4 regulates TS expression, high levels of p16INK4A would be expected to decrease TS levels and to sensitise cells to anti-TS drugs.…”
Section: Discussionsupporting
confidence: 67%
“…resection specimens and observed significant overexpression of p16 in resection specimens from patients who had a response to 5-FU-based chemotherapy compared with nonresponders and controls. 54 Our major novel findings suggest that negative p16 expression evaluated in lymph nodes, rather than in primary tumors, from patients with stage III disease who received adjuvant therapy is a highly adverse prognostic indicator. In fact, negative p16 expression was related to worse survival in both pT3 and pT4 disease and was independent of patient age, LNR, performance status, treatment with folic acid, and chemotherapy regimen.…”
mentioning
confidence: 80%
“…However, whereas FdUrd and the other downstream metabolites of FdCyd are incapable of inhibiting DNA methyltransferase, they do have potent cytotoxic activity, and 5-FU and FdUrd are frequently used therapeutically (32,33). In addition, their cellular effects result in cell cycle arrest, which inherently prevents incorporation of FdCyd into DNA (34). There still exists the possibility of metabolite formation via deoxycytidylate deaminase (dCMP deaminase; Fig.…”
Section: Discussionmentioning
confidence: 99%